Pengaruh Promosi Media Digital Dan Word Of Mouth Terhadap Keputusan Nasabah Dalam Menggunakan BSI Mobile Dari Bank Syariah Indonesia. - Rozza, Sylvia; Lufna Salsabila, Thalia (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
Indonesia has experienced rapid economic and communication technological development which. is utilized by the world of Islamic banking to improve the quality of their products. One of the efforts is to provide Sharia Mobile Banking services. Bank Syariah Indonesia (BSI) is a sharia bank from corporation of Bank BNI Syariah, Bank BRI Syariah, and Bank Syariah Mandiri which was newly established in Indonesia in 2021. However, the number of BSI Mobile users is still relatively low. The purpose of this study was to determine the effect of digital media promotion and word of mouth on customer decisions in using BSI Mobile. The data analysis method used is multiple linear regression on 100 respondents using BSI Mobile in the Greater Jakarta area. The results of this study are partially and simultaneously digital media promotions and word of mouth have a significant positive effect on customer decisions in using BSI Mobile. The novelty in this research is the framework which analyse the influence of digital media promotion and word of mouth on customer decisions to use BSI mobile in Indonesia cannot be found. This research is expected to be an input for BSI in optimizing its promotion strategy in order to improve customer decisions in using BSI Mobile. This can be done by increasing promotions on social media such as websites, Instagram, Twitter, Facebook, and other media Keywords: Customer Decisions; BSI Digital Media Promotion; Word of Mouth